Collaborative Heterogeneous Underlaying Cellular Networks:Fundamental Theories and Key Technologies - Mingxin Zhou; Chen Xu; Kun Yang; Yang Yu; Kaifei Zhao; Lingyang Song (Dianxin kexue)
The research progress and contributions about the fundamental theories and key technologies of collaborative heterogeneous underlaying cellular networks were introduced. The fundamental theories include the architecture, capacity region, connectivity problem of the collaborative heterogeneous underlaying networks, while the key technologies consist of interference management, wireless resource management, and exploration and utilization of vacant radio-frequency spectrum. The current study shows that D2D communication in collaborative heterogeneous underlaying cellular networks will become the key technology in the next-generation cellular communication systems because it can further improve the spectrum efficiency and system capacity in wireless communication networks.